Ethnomathematical Analysis of Processing Techniques in Alame and Lemang: Traditional Foods of Padang Lawas - Rizki Wahyudi Nasution; Eka Khairani Hasibuan (MASI Mandiri Edukasi, 2025)
Limited student understanding of contextual mathematical concepts remains a key issue in learning. This study aims to identify and analyze mathematical concepts in the preparation of traditional foods Alame and Lemang from Padang Lawas using an ethnomathematics approach. A qualitative descriptive-exploratory method was employed, with data collected through observation, semi-structured interviews, and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña and validated through triangulation and member checking. The results indicate that Lemang preparation involves spatial geometry, geometric transformations, and heat distribution, while Alame applies ratios and proportions of ingredients, traditional measurement, and time and temperature estimation. Both techniques reflect principles of algorithm, order, and efficiency. These findings confirm that traditional culinary practices can serve as contextual mathematics learning media while contributing to the preservation of local culture.